Analisis Parameter EC dan TDS pada Beberapa Sumber Air di Pulau Ambon sebagai Konteks Praktikum Fisika - Grimaldy Rooy Latumeten; Hendry Izaac Elim (Jurnal Pendidikan dan Ilmu Fisika, 2026)
Groundwater quality is crucial for health, particularly for drinking water, with physical parameters such as Electrical Conductivity (EC) and Total Dissolved Solids (TDS) as key indicators. This study aims to examine the physical quality of groundwater sources in several locations on Ambon Island and identify their potential as contextual physics lab teaching materials. The method used was an experiment, with groundwater samples taken from Nusaniwe District (urban) and Salahutu District (rural), as well as bottled drinking water (AMDK) samples as a comparison. EC and TDS measurements were conducted using a calibrated EC/TDS meter, following standard procedures and three repetitions. The results showed that all groundwater samples had EC values ​​below 400 µS/cm and TDS values ​​below 300 mg/L, making them suitable for drinking water based on Indonesian Minister of Health Regulation No. 2 of 2023 and WHO guidelines. The Salahutu groundwater sample showed the best quality with an EC of 101.33 µS/cm and a TDS of 49.67 mg/L, while the Nusaniwe sample had higher values ​​due to anthropogenic activity. The relationship between EC and TDS was a very strong linear (R² = 0.9987) with a regression equation of y = 0.5109x – 1.487. In conclusion, the groundwater samples on Ambon Island meet the physical requirements for drinking water, and the varying EC-TDS data have the potential to be developed into teaching materials for physics labs, particularly for topics such as electrical conductivity of solutions, ion mobility, linear regression, and contextual data analysis skills.